EVALUASI TEKNIK PENANGANAN SWABAKAR PADA STOCKPILE DI PT BUDI GEMA GEMPITA, LAHAT, SUMATERA SELATAN - Pingky Yuito; Ridho Yovanda; Aris Susilo (Jurnal Humaniora & Sosial Sains, 2025)
This study aims to conduct an in-depth evaluation of the current firefighting techniques at PT Budi Gema Gempita. To achieve this objective, a combined research method was used, including field observations to observe stockpiling and handling practices, periodic temperature measurements using an industrial thermogun to detect hot spots, interviews with operators to understand standard procedures, and secondary data analysis. The results identified that the main triggering factors for firefighting at the site were a combination of internal coal characteristics, namely high levels of Total Moisture (31.36%) and volatile matter (40.45%), which were exacerbated by storage periods exceeding two months. Field temperature measurements successfully detected a critical point in Seam 6 with a temperature reaching 72°C, indicating an advanced oxidation process that requires immediate treatment. This study evaluated two treatment methods: the use of an excavator alone and a combination of an excavator and chemical solutions. Conventional treatment, which involved dismantling and cooling the pile using an excavator, proved to be quite effective for heat dissipation. However, the combination method of spraying chemical liquid after dismantling shows far superior results, as it is able to reduce the temperature drastically and more quickly while stopping the oxidation process by coating the coal surface, thus offering a more efficient and complete solution.